Analysis of the Coupling Between CHP and EHP in an Office Building Applied to the Italian Energy Market. (November 2016) - Magnani, Sandro; Danti, Piero; Pezzola, Lorenzo
Abstract: The increasing need for energy and cost efficient solutions for thermal and electric supply is giving new life to CHP plants, even for small power sizes. It is renowned that the optimal application of a CHP plant is to satisfy as much as possible both the electricity and the thermal requirements of the loads, but the frequent applicative context, especially for residential and/or tertiary buildings, is unbalanced towards the thermal needs, so that the sizing of the CHP is determined by the electric loads, at least in the Italian tariff structure context, with the consequence that the generator is relatively small and, consequently, the installation costs represent a consistent part of the capital investment. The increasing level of the performance of the electric heat pump can sensitively minimize the former issue: the combination between a CHP and an EHP can led to a larger size of the co-generative unit, whose exceeding power output can feed the heat pump so that to efficiently satisfy most of the thermal loads of the plant. In this paper an application case referred to an office building is presented: the optimal size of the system will be discussed, and the economic results (in terms of PBT and NPV) of the management of the plant compared with other commonly exploited solutions: Conventional supply, with the heat produced by a gas boiler, the cooling from an electric chiller, and the electricity purchased by the grid; Optimal sizing of the CCHP based on the heating loads duration curve, with the engine operated in thermal-led; Optimal sizing of the CCHP based on the electric loads duration curve, with the engine operated in power-led. The environment performance will be discussed as well, focusing on the comparison between the different solutions in terms of equivalent CO2 emissions and primary energy consumptions.